2019
DOI: 10.1186/s12889-019-7826-6
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and associated risk factors in Burkina Faso: results from a population-based cross-sectional survey

Abstract: BackgroundTobacco is a leading preventable cause of non-communicable diseases (NCDs). Studies characterizing the prevalence of tobacco use in low-income countries are lacking. This study describes the prevalence of tobacco use in Burkina Faso and its associated factors.MethodsData from the 2013 Burkina Faso World Health Organization (WHO) Stepwise approach to Surveillance (STEPS) were analyzed. The prevalence of any tobacco product use, cigarette smoking, and other tobacco use was calculated. Logistic regressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
(21 reference statements)
0
17
1
Order By: Relevance
“…This result was in line with the previous studies in Ethiopia, Tanzania, Brazil, and Burkina Faso. 8 , 23 , 33–35 In contrast, a study in Kenya reported that the majority of smokers were in younger age groups. 36 The reason for higher tobacco use in older women could be due to older women might have long smoking histories, previous unsuccessful quitting attempts, and doubts about the advantages of leaving tobacco use.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This result was in line with the previous studies in Ethiopia, Tanzania, Brazil, and Burkina Faso. 8 , 23 , 33–35 In contrast, a study in Kenya reported that the majority of smokers were in younger age groups. 36 The reason for higher tobacco use in older women could be due to older women might have long smoking histories, previous unsuccessful quitting attempts, and doubts about the advantages of leaving tobacco use.…”
Section: Discussionmentioning
confidence: 94%
“…This finding was consistent with many previous study results. 22 , 33 , 40 This can be due to poly-substance use behaviors. Khat chewing, alcohol consumption, and tobacco use are closely connected ceremonies, and consuming one of them could lead to the use of another one.…”
Section: Discussionmentioning
confidence: 99%
“…45 The methodology of this survey is explained elsewhere. [33][34][35] This survey was representative at the national and regional levels. Briefly, participants were randomly selected using a clusterstratified three-stage sampling procedure.…”
Section: Data Source: Who Stepwise Surveymentioning
confidence: 99%
“…32 High prevalences of some CVD risk factors (hypertension, diabetes, and tobacco use) have been reported. [33][34][35] Given the high prevalence of these CVD risk factors, atherosclerotic CVD might be the most important public health concern. 36 Despite the importance of CVD risk to inform policymakers and health authorities in understanding the magnitude of the future distribution of CVDs in the population, no study has evaluated this score at the population-wide level in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco smoking is the leading preventable cause of premature death in both developing and developed countries (WHO, 2015;Reitsma, et al, 2017;Jetty et al, 2017;Bonnechère et al, 2019). Deadly diseases associated with tobacco abuse include lung cancer, pneumonia, vascular diseases, age-related muscle degeneration, respiratory heart disease, chronic obstructive lung disease, stroke, aortic aneurysm and ischaemic heart disease (McGinnis & Foege, 1993;Wald & Hackshaw, 1996;Ockene & Miller, 1997;Jetty et al, 2017).…”
Section: Introductionmentioning
confidence: 99%